Current Trends and Common Themes in Publications Concerning Private Equity Investment Into Orthopaedic Surgery Practices: Key Takeaways - Abtahi Tishad, BS; Ryan Skelly, BS, MBA; Griffin Stinson, BS; MaryBeth Horodyski, EdD; Rull James Toussaint, MD, FAOA (JBJS Open Access, 2024)
Introduction:. Private equity (PE) investment in health care has increased more than 250% between 2010 and 2020. This is mirrored by an increasing number of published materials in medical journals. The objective of our study was to identify and characterize trends and key themes seen within publications discussing the topic of PE investment into orthopaedic surgery practices and bias within those publications. Methods:. The inclusion criteria for our study required an article to be published between the years 2003 and June 2024 and to contain the phrase “orthopaedic surgery” or “orthopedics” in addition to “PE” or “PE investment.” Based on these parameters, 15 articles met the criteria for inclusion. Articles were then evaluated to assess various themes related to general views expressed regarding PE firms, reasons for PE attraction to orthopaedics, and most cited positives/negatives of PE investment and potential conflicts of interest with respect to underlying relationships/associations with PE firms at the time of publication. Results:. Of the 15 publications meeting the inclusion criteria, 4 (26.7%) expressed positive views on the topic of PE ownership of orthopaedic practices, while 4 (26.7%) expressed a neutral view and 7 (46.7%) expressed a negative outlook. Four (26.7%) of the articles had authors who were either employed or had ownership in a practice that was purchased by a PE firm. Of these 4 articles, none disclosed this potential conflict of interest. Three of the 4 articles had either a positive or neutral view of PE. The most cited reason for PE attraction to orthopaedics was revenue from ancillary services. The most cited upside of PE transactions was the possibility of benefiting from economies of scale, while the most cited downside was the misalignment of incentives. Conclusion:. The plurality of present studies views PE transactions negatively (46.7%). Our research unveiled 4 studies with undisclosed conflicts of interest (26.7%). In addition, orthopaedic surgeons should be wary of the numerous downsides of PE transactions, such as the misaligned incentives between themselves and PE firms. Clinical relevance:. Independent orthopaedic practices should be critical of the literature when evaluating the merits of potential partnerships with PE firms.